An expanded record of proxy data in the uppermost Permian Changxing Fm. in the Meishan C section - Ryosuke Saito; Lars Wörmer; Heidi Taubner; Kunio Kaiho; Satoshi Takahashi; Li Tian; Masayuki Ikeda; Roger E Summons; Kai-Uwe Hinrichs (PANGAEA, 2022)
The end-Permian mass extinction (EPME) is the severest mass extinction event in the Phanerozoic eon. According to the general hypothesis, the mass extinction was caused mainly by the concurrent emplacement of the Siberian Traps Large Igneous Province. However, given that Siberian Traps eruptions are thought to have lasted for at least 900 kyr, it is still unclear what caused the much shorter episodes of 60±48 kyr mass extinction. Detailed, high-resolution (mm-scale or higher) investigations of tracers for volcanic activity and ecosystem collapse are thus needed to clarify their causal relation. In order to overcome this issue, we applied submillimeter-resolution Mass Spectrometry Imaging (MSI) of organic compounds on sedimentary rocks deposited spanning the EPME. We rely on sedimentary rock pieces of 20 cm length of the uppermost Permian Changxing Fm sampled from the Meishan C section (31°4 extquotesingle36.74 extquotesingle extquotesingleN, 119°41 extquotesingle52.80 extquotesingle extquotesingleE), south China. MSI analysis was conducted using a 7T solarix XR Fourier transform-ion cyclotron resonance-mass spectrometer (FT-ICR-MS) equipped with a Smartbeam II laser. In addition, we paired MSI analysis with records of elemental composition at submillimeter resolution obtained by micro-X-ray fluorescence spectroscopy (micro-XRF) to provide insight into the contribution of clastic material and provenance as well as redox conditions. The dataset presents depth, a relative abundance of 4- to 7-ringed polyaromatic hydrocarbons (PAH) and C2-dibenzofuran, and the ratio of 7-ringed vs. 5-ringed PAHs (PAH 7/5), counts values of aluminum, sulfur, and iron. Moreover, we provide an abundance of 4- to 7-ringed PAH and C2-dibenzofuran, the PAHs 7/5, and βα/(βα +αβ) ratios for C30 hopane isomers for seven samples in cm resolution by gas chromatography-mass spectrometry (GC-MS).